The Effect of Problem Possing Assisted Mind Mapping on Communication and Connection Skill in Terms of Cognitive Style - Fitriana Eka Chandra (Universitas Islam Jember, 2017)
The purpose of this research was to investigate the effects of Problem Posing learning facilitated by Mind Mapping toward mathematical connection and mathematical communication abillity based on students’ cognitive style. Totally, there were 106 students involved in the study which comprised of 42 students from VIIE class of SMPN 7 Jember as experimental group (PPMM class), 42 students from VIIF class of SMPN 7 Jember as the first control group (PP1 class) and 32 students from VIID class of SMPN 1 Arjasa as the second control group (PP2 class). Experimental group was taugh using problem posing approaches facilitated by mind mapping tehnique (PPMM class) and control group was taugh only using problem possing approaches (PP class). Before giving the treatment, students was given test to know the kind of cognitive style that they have. There are two kind of student’s cognitive style in this paper i.e. field-dependent and field-independent cognitive style.The instrumens of the study were a Group Embeded Figure Test (GEFT) and Mathematical Connection and Mathematical Communication abillity Test. The study found that student’s mathematical connection and mathematical communication abillity of PPMM class are better than PP class. Moreover, mathematical connection and mathematical communication abillity of field independent students is better than field dependent students. Keywords: problem possing, mind mapping, cognitive style, and mathematical connection and mathematical communication abillity